In2O3 carrier material, preparation method thereof, sensitive sensing assembly and application
By oxidizing and nitriding the MIL-68 to generate In2O3 carrier material, it is used for fuel cell gas sensors, and the problems of high nitrogen dioxide detection cost and poor catalyst dispersion in the prior art are solved, and high sensitivity and rapid response are achieved and good detection effect.
Patent Information
- Application Number
- CN202411299441.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing fuel cell-type gas sensors have problems such as high cost and poor dispersion of precious metal catalysts when detecting nitrogen dioxide, making it difficult to achieve efficient and portable detection.
In2O3 nanorods were generated by oxidizing the porous MIL-68, and the nitrogen-oxygen ratio was adjusted during the nitriding treatment to form In2O3 carrier material as electrode material, which was used to prepare sensitive sensing components to improve sensitivity to nitrogen dioxide and Selective.
High sensitivity detection for low concentrations of nitrogen dioxide is achieved, with fast response, short recovery time, high stability and good moisture resistance, reducing costs and improving selectivity.
Smart Images

Figure CN119191339A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cell type gas sensors, and is particularly concerned with an In 2 O 3 Carrier material and preparation method thereof, sensitive sensing component and application. Background Art
[0002] With the rapid development of global economy and industrialization, the emission of nitrogen oxides, especially nitrogen dioxide, has increased significantly, which has attracted widespread attention. Nitrogen dioxide not only plays a key role in the ozone process, but also has many impacts on the environment, including wetland ecological damage, reduced atmospheric visibility, surface water acidification and eutrophication, and increased toxin content in water bodies, posing a threat to aquatic life. Therefore, it is crucial to develop a method to effectively detect the content of nitrogen dioxide in the environment.
[0003] However, the current NO2 detection technology on the market faces the dual challenges of portability and cost. Traditional PEM fuel cell-based gas sensors rely on precious metal catalysts, such as platinum, which not only increases the cost, but also the problem of uniform dispersion of precious metal particles and the resulting poor selectivity needs to be solved urgently. Summary of the invention
[0004] 1. Technical issues to be solved
[0005] In view of the deficiencies in the prior art, the present invention provides an 2 O 3 The carrier material and its preparation method, sensitive sensing component and application, through the nitridation-treated metal-organic framework to regulate the nitrogen-oxygen ratio, make the derived indium oxide replace the precious metal catalytic material as the electrode material of the gas sensor with efficient nitrogen dioxide gas sensing performance, solve the problems raised in the above background technology.
[0006] (II) Technical solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] According to a first aspect of the present invention, there is provided an 2 O 3 The preparation method of the carrier material comprises the following method:
[0009] S1. First, MIL-68 is subjected to heat preservation treatment, and then subjected to oxidation treatment to obtain In 2 O 3 Nanorods;
[0010] S2, In 2 O 3The nanorods were placed in a high-speed nitriding furnace and nitrided in an ammonia atmosphere to obtain In 2 O 3 Carrier material.
[0011] Preferably, in step S1, the temperature of the heat preservation treatment is 100-150° C., and the time is 1-5 hours.
[0012] Preferably, in step S1, the oxidation treatment conditions are: heating to 500-600° C. at a heating rate of 5° C. / min and oxidizing for 2-3 hours.
[0013] Preferably, in step S1, the preparation method of MIL-68 is as follows: (NO 3 ) 3 ·xH 2 O and 1,4-phthalic acid are dissolved in excess dimethylformamide, treated with ultrasound, heated in an oil bath, and the white precipitate is collected, washed, and dried to obtain the MIL-68.
[0014] Preferably, the (NO 3 ) 3 ·xH 2 The mass ratio of O to the 1,4-phthalic acid is 1:1.
[0015] And / or, the ultrasonic treatment is applied for 10 to 20 minutes;
[0016] And / or, the oil bath heating time is 30 to 60 minutes;
[0017] And / or, the washing agent used in the washing is ethanol, and the number of washing times is 3 to 5 times;
[0018] And / or, the drying temperature is ≤60°C.
[0019] Preferably, in step S2, the nitriding treatment is carried out under the condition of: nitriding treatment at 500° C. for 20 to 80 min under the condition of an ammonia flow rate of 100 mL / min.
[0020] Further preferably, in step S2, the nitridation treatment is performed at 500° C. for 20 to 40 min under the condition of an ammonia flow rate of 100 mL / min.
[0021] According to a second aspect of the present invention, there is provided a 2 O 3 In obtained by the preparation method of the carrier material 2 O 3 The carrier material, the In 2 O 3 The carrier material has a cubic crystal structure, the space group is I a-3, and the lattice parameter is The nitrogen-oxygen ratio is 0.21-4.62%.
[0022] According to a third aspect of the present invention, a method for preparing a sensitive sensor component is provided, comprising: 2 O 3 The carrier material, 20 μL of a 5% mass concentration Nafion solution and 200 μL of isopropanol were ultrasonically treated to obtain a dispersed material solution, which was dropped onto carbon paper and treated at 90°C and 1 MPa for 90 seconds to form a sensitive sensing component, wherein In 2 O 3 The carrier material is selected from the above In 2 O 3 The preparation method of the carrier material is obtained.
[0023] According to a fourth aspect of the present invention, there is provided application of a sensitive sensor component obtained according to the above-mentioned method for preparing the sensitive sensor component in a fuel cell type gas sensor.
[0024] (III) Beneficial effects
[0025] The present invention provides an In 2 O 3 Carrier material and preparation method thereof, sensitive sensing component and application.
[0026] It has the following beneficial effects:
[0027] 1. In this solution 2 O 3 The preparation method of the carrier material is to derive In by oxidizing porous MIL-68 2 O 3 Nanorods, then nitrided to regulate In 2 O 3 The nitrogen-oxygen ratio of the carrier material optimizes the In 2 O 3 The crystal structure of the nanostructured carbonyl phosphate improves its sensitivity and selectivity to nitrogen dioxide.
[0028] 2. In fuel cell type gas sensors, In 2 O 3 The sensitive sensing component made of the carrier material has high sensitivity and selectivity to low-concentration nitrogen dioxide, and has the advantages of fast response speed, short recovery time, high stability, and good moisture resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 For the present invention 2 O 3 Schematic diagram of the synthetic route of the carrier material;
[0030] Figure 2 XRD diagrams of the carrier materials prepared in Examples 1-4 and Comparative Example 1 of the present invention;
[0031] Figure 3 In prepared in Example 1 of the present invention 2 O 3 N-40min refined XRD pattern;
[0032] Figure 4 In prepared in Example 1 of the present invention 2 O 3 Schematic diagram of the atomic structure of N-40min;
[0033] Figure 5 The fuel cell type gas sensor prepared by using the carrier materials obtained in Examples 1-4 and Comparative Example 1 of the present invention is 10ppm NO 2 Graph of current changes corresponding to gas concentration;
[0034] Figure 6 For the present invention 2 O 3 N-40min fuel cell type gas sensor and In 2 O 3 Comparison of baseline current of fuel cell type gas sensor in air;
[0035] Figure 7 The fuel cell type gas sensor prepared by using the carrier materials obtained in Examples 1-4 and Comparative Example 1 in the present invention is subjected to different NO 2 Schematic diagram of the response of gas concentration;
[0036] Figure 8 For the present invention 2 O 3 N-40min fuel cell type gas sensor in different NO 2 Specific dynamic curves under gas concentration;
[0037] Fig. 9 For the present invention 2 O 3 N-40min fuel cell type gas sensor and In 2 O 3 Fuel cell type gas sensor for NO 2 Schematic diagram of positive linear response in the range of 100ppb to 10ppm;
[0038] Fig.10 For the present invention 2 O 3 N-40min fuel cell type gas sensor at 10ppm NO2 Schematic diagram of the response of 6 cycle tests under gas concentration;
[0039] Fig.11 For the present invention 2 O 3 N-40min fuel cell type gas sensor at 10ppm NO 2 Schematic diagram of 30 cycle test responses under gas concentration;
[0040] Fig.12 For the present invention 2 O 3 N-40min fuel cell type gas sensor and In 2 O 3 Schematic diagram of the response current of the fuel cell type gas sensor under different humidity conditions;
[0041] Fig.13 The fuel cell type gas sensor prepared by the carrier material obtained in Examples 1-4 and Comparative Example 1 of the present invention is NO 2 Schematic diagram of response and recovery speed;
[0042] Fig.14 This is a schematic diagram of the reaction of a fuel cell type gas sensor prepared by using the carrier materials obtained in Examples 1-4 and Comparative Example 1 of the present invention to different gases. DETAILED DESCRIPTION
[0043] In order to better illustrate the content of the present invention, a detailed description is given below in conjunction with specific embodiments.
[0044] Example 1
[0045] This example prepares an In 2 O 3 Support materials, synthesis routes such as Figure 1 As shown:
[0046] Synthesis of MIL-68 precursor: 300 mg of (NO 3 ) 3 ·xH 2 O and 300 mg of 1,4-benzenedicarboxylic acid were dissolved in 40 mL of DMF, and after ultrasonic treatment for 10 min, the mixture was placed in an oil bath and heated for 30 min. During the heating process, the solution gradually became turbid and precipitated in the form of a white solid. After cooling to room temperature, the white precipitate was collected, washed with ethanol three times, and dried at 60 °C to obtain a MIL-68 precursor.
[0047] In 2 O 3Synthesis of nanorods: The MIL-68 precursor was kept at 120 °C for 2 h, and then heated to 500 °C at a heating rate of 5 °C / min for 2 h to obtain In 2 O 3 Nanorods;
[0048] In 2 O 3 Synthesis of carrier materials: In 2 O 3 The nanorods were placed in a high-speed nitriding furnace, and ammonia was repeatedly injected to exhaust the air in the high-speed nitriding furnace. Then, the flow rate of ammonia was adjusted to 100 mL / min, and the temperature was raised to 500 °C for nitriding treatment and maintained for 40 min to obtain In 2 O 3 Carrier material, denoted as In 2 O 3 N-40min.
[0049] Example 2
[0050] The preparation method of this embodiment is the same as that of embodiment 1, except that 2 O 3 During the synthesis of the support material, the nitridation treatment time was 20 min, and the obtained product was recorded as In 2 O 3 N-20min.
[0051] Example 3
[0052] The preparation method of this embodiment is the same as that of embodiment 1, except that 2 O 3 During the synthesis of the support material, the nitridation treatment time was 60 min, and the obtained product was recorded as In 2 O 3 N-60min.
[0053] Example 4
[0054] The preparation method of this embodiment is the same as that of the embodiment, except that 2 O 3 During the synthesis of the support material, the nitridation treatment time was 80 min, and the obtained product was recorded as In 2 O 3 N-80min.
[0055] Comparative Example 1
[0056] The difference between this comparative example and Example 1 is that no nitriding treatment is performed and the obtained product is recorded as In 2 O 3 .
[0057] By performing XRD analysis on the products of Examples 1 to 4 and Comparative Example 1, it is found that Figure 2 As shown, the diffraction peak at 30.58° can be attributed to In 2 O 3 (PDF#06-0416) (222) crystal plane, and no obvious shift of the peak position was observed, indicating that the number of single atoms entering the lattice is relatively small.
[0058] In Example 1 2 O 3 For example, N-40min, XRD refinement, such as Figure 3 and Figure 4 As shown, In 2 O 3 N-40min has a cubic crystal structure with space group I a-3, R wp is 5.2%, and the lattice parameter is It can be seen that the fitting diagram is in good agreement with the original XRD data, and the unit cell parameters change after single atoms replace oxygen atoms.
[0059] In order to accurately prove the actual nitrogen and oxygen ratio, the material was subjected to elemental analysis and normalized. 2 O 3 The nitrogen-oxygen ratio of the N-40min sample was 0.31%, which was consistent with the ratio after the refinement treatment. The nitrogen-oxygen ratios of Examples 2 to 4 are shown in Table 1;
[0060] Table 1
[0061]
[0062]
[0063] Application Examples
[0064] Take 10 mg of the products prepared in Examples 1 to 4 and Comparative Example 1, and treat them with 20 μL of a mixture of a 5% mass concentration of Nafion solution and 200 μL of isopropanol by ultrasonic treatment to obtain a dispersed substance solution, drop the substance solution on carbon paper, use a PTFE film as a protective layer, treat the carbon paper with the substance solution at 90°C and 1 MPa for 90 seconds to obtain a sensitive sensor component, trim the sensitive sensor component into a disc with a diameter of 1 cm, and combine it with two electrodes by hot melt adhesive to form a compact fuel cell. Then use hot melt adhesive to firmly stick a container filled with deionized water-soaked cotton to the cathode of the fuel cell. During operation, the working electrode is exposed to the target gas, and the cathode is sealed in a container filled with humid air.
[0065] The test adopts the traditional static method, which is to place a certain volume of NO2 Gas detection of different concentrations was achieved by injecting into a 250ml gas collection bottle through a syringe. The test was carried out under laboratory conditions (22±2℃, 45±3%RH) using a multi-channel potentiostat (CHI1030C, Shanghai Chenhua Instrument Co., Ltd.) in "it" mode. The corresponding current ΔI is the difference between I1 and I2 (I1=response current, I2=baseline current). The 90% value of ΔI is used to characterize the response and recovery time of adsorption and desorption. The slope obtained by linear fitting of ΔI and concentration represents the sensitivity of the sensor. LiCl, MgCl 2 Mg(NO 3 ) 2 , NaCl, KCl and KNO 3 The relative humidity (RH) of the saturated solutions were 11%, 33%, 54%, 75%, 85% and 95%, respectively.
[0066] according to Figure 5 As shown, when exposed to 10 ppm NO 2 The corresponding current of the fuel cell type gas sensor prepared by using different carrier materials increases. The In 2 O 3 At N-40min, the response current of the fuel cell type gas sensor is the highest, reaching 771nA. The response current increases first and then decreases with the increase of nitridation time.
[0067] Separately collect the data using In 2 O 3 Fuel cell type gas sensor prepared by N-40min and using In 2 O 3 The baseline current changes of the prepared fuel cell type gas sensor in air, such as Figure 6 As shown, based on the root mean square deviation (RMSD) method, In 2 O 3 Fuel cell type gas sensor and In 2 O 3 The detection limits of N-40min fuel cell type gas sensors are 5ppb and 3ppb respectively. Since lower current fluctuations help to identify weaker sensor response signals, In 2 O 3 N-40min fuel cell type gas sensor for NO 2 Gas is more responsive.
[0068] according to Figure 7 As shown, with NO 2As the gas concentration increases, the response values of the fuel cell-type gas sensors prepared with different carrier materials also increase accordingly, and show a good linear relationship. It can be seen that In 2 O 3 The response current of the N-40min fuel cell gas sensor is the highest at any concentration, which shows that the optimal nitridation time is 40 minutes. The specific dynamic curve is as follows: Figure 8 shown.
[0069] according to Fig. 9 As shown, In 2 O 3 Fuel cell type gas sensor and In 2 O 3 N-40min fuel cell type gas sensor for NO 2 It shows positive linear response in the range of 100ppb to 10ppm, and In 2 O 3 The sensitivity of N-40min fuel cell type gas sensor (73.61nA / ppm) is higher than that of In 2 O 3 Fuel cell type gas sensor (15.12nA / ppm).
[0070] according to Fig.10 As shown, 10ppm NO 2 In 2 O 3 The N-40min fuel cell type gas sensor was repeatedly tested and it can be seen that In 2 O 3 The N-40min fuel cell-based gas sensor showed good repeatability in six cycle tests.
[0071] according to Fig.11 As shown, In 2 O 3 Fuel cell type gas sensor and In 2 O 3 N-40min fuel cell type gas sensor for 10ppm NO 2 Response over time within 30 days. 2 O 3 The N-40min fuel cell-type gas sensor can still maintain a high response current (758nA) after being exposed to air for one month, and has excellent sensing performance and stability.
[0072] The In 2 O 3 Fuel cell type gas sensor and In 2 O3 The response current of the N-40min fuel cell type gas sensor under the corresponding humidity conditions (33% to 95%) is based on Fig.12 As shown, In 2 O 3 The response current of the fuel cell type gas sensor during N-40min has hardly changed and remains at about 4nA. 2 O 3 N-40min fuel cell type gas sensor has excellent moisture resistance. 2 O 3 N-40min has a unique nitrogen-oxygen ratio. Ambient humidity will cause the active sites of oxygen on the surface of the sensing material to be occupied by water molecules, thereby weakening the electron transfer ability. Part of the oxygen is replaced by nitrogen, which will weaken the adsorption performance of water molecules, thereby ensuring the normal transfer of electrons and improving the moisture resistance of the material.
[0073] In practical applications of sensors, the response time determines the detection efficiency of gas sensors. 2 The response and recovery speed of all devices were measured at room temperature for 10ppm NO 2 Response / recovery time (τ res / τ recov ).like Fig.13 As shown, In 2 O 3 N-40min fuel cell type gas sensor has fast response and recovery speed (5 / 16s), which is much better than In 2 O 3 Fuel cell type gas sensor (21 / 30s).
[0074] Since it is crucial for gas sensors to identify specific target gases in complex working environments, the selectivity of the material-based sensor was tested to evaluate the anti-interference ability of the device. The fuel cell-type gas sensors prepared using the carrier materials obtained in Examples 1-4 and Comparative Example 1 were tested for their responses to different gases. The test gases included nitrogen dioxide, acetone, hydrogen sulfide, carbon monoxide, methanol, ammonia, ethanol, hydrogen and toluene. The test results are shown in Figure 1. Fig.14 As shown, the fuel cell type gas sensor is 2 The response value of In is the highest, while it has almost no response to other gases. 2 O 3 N-40min fuel cell type gas sensor for NO 2 The best selectivity.
[0075] Through the above comprehensive tests, it can be seen that the In obtained by the preparation method of the present invention 2 O3 The carrier material, when used in fuel cell type gas sensors, can have high sensitivity and selectivity to low concentration nitrogen dioxide, and also has the advantages of fast response speed, short recovery time, high stability, and good moisture resistance.
[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an In2O3 carrier material, characterized in that: The following methods are included: S1, firstly subjecting MIL-68 to heat preservation treatment, and then subjecting it to oxidation treatment to obtain In2O3 nanorods; S2. Placing the In2O3 nanorods in a high-speed nitriding furnace for nitriding treatment in an ammonia atmosphere to obtain an In2O3 carrier material.
2. The method for preparing an In2O3 carrier material according to claim 1, characterized in that: In step S1, the temperature of the heat preservation treatment is 100-150°C and the time is 1-5 hours.
3. The method for preparing an In2O3 carrier material according to claim 1, characterized in that: In step S1, the oxidation treatment conditions are: heating to 500-600°C at a heating rate of 5°C / min for oxidation for 2-3h.
4. The method for preparing an In2O3 carrier material according to claim 1, characterized in that: In step S1, the preparation method of the MIL-68 is as follows: (NO3)3·xH2O and 1,4-phthalic acid are dissolved in excess dimethylformamide, ultrasonically treated, heated in an oil bath, white precipitates are collected, washed, and dried to obtain the MIL-68.
5. The method for preparing an In2O3 carrier material according to claim 4, characterized in that: The mass ratio of the (NO3)3·xH2O to the 1,4-phthalic acid is 1:
1. And / or, the ultrasonic treatment is applied for 10 to 20 minutes; And / or, the oil bath heating time is 30 to 60 minutes; And / or, the washing agent used in the washing is ethanol, and the number of washing times is 3 to 5 times; And / or, the drying temperature is ≤60°C.
6. The method for preparing an In2O3 carrier material according to claim 1, characterized in that: In step S2, the nitriding treatment conditions are: nitriding treatment at 500° C. for 20 to 80 min under the condition of an ammonia flow rate of 100 mL / min.
7. The method for preparing an In2O3 carrier material according to claim 1, characterized in that: In step S2, the nitriding treatment conditions are: nitriding treatment at 500° C. for 20 to 40 min under the condition of an ammonia flow rate of 100 mL / min.
8. An In2O3 carrier material obtained by the preparation method of an In2O3 carrier material according to any one of claims 1 to 7, characterized in that: The In2O3 carrier material has a cubic crystal structure, a space group of Ia-3, and a lattice parameter of The nitrogen-oxygen ratio is 0.21-4.62%.
9. A method for preparing a sensitive sensor component, characterized in that: A mixture containing 10 mg of In2O3 carrier material, 20 μL of Nafion solution with a mass concentration of 5% and 200 μL of isopropanol is ultrasonically treated to obtain a dispersed material solution, and the material solution is dropped on carbon paper and treated at 90°C and 1 MPa for 90 seconds to form a sensitive sensing component, wherein the In2O3 carrier material is selected from the In2O3 carrier material obtained by the preparation method according to any one of claims 1 to 7 or the In2O3 carrier material according to claim 8.
10. Application of the sensitive sensor component obtained by the preparation method according to claim 9 in a fuel cell type gas sensor.
Citation Information
Patent Citations
Silver-modified micron tubular indium oxide nitrogen dioxide gas-sensitive material and preparation method thereof
CN113740383A
Hollow tubular In2O3 photoelectrode material and preparation method and application thereof
CN117886351A
MOF-derived Au-loaded In2O3 nanotube and preparation method thereof
CN117983177A
In-MOF derivative material and preparation method and application thereof
CN118290762A
